Becoming agile : how the SEAM approach to management builds adaptability - Worley, Christopher G. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2015)
This short-format case study of the French company Brioche Pasquier highlights how one organization successfully implemented the principles of agility using the socio-economic approach to management, detailing each step of the process and describing how every decision brought the goal within reach. From overarching policy to day-to-day procedure, the story provides a clear example of how an agile organization is developed, giving readers a foundation upon which to implement similar changes in their own organization. Smart companies understand the importance of agility, but identifying where and how to initiate those first steps often leads to paralysis by analysis. This case study allows readers to learn from an organization that got through the inertia and put the principles of agility into action, with incredible results. --
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Organizational change; Organizational effectiveness; Management; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; Management; Organizational change; Organizational effectiveness; Electronic books; Electronic books